Wayfinding and Imageability of Daily Commuters in Ferry Terminal: Case Study of Jalan Tun Uda and Penang Sentral, Penang - Najmuddin, Abdul Munir; Nordin, Jestin; Mohd Salleh, Mohd Najib; Mohd Razif, Farhana (MAJ - Malaysia Architectural Journal, 2020)
Public transportations such as taxis, buses, trains, aeroplanes, boats, or even ferries are part of the methods of transportation for millions of people to commute to their workplaces, schools, visiting, or to their places of interest. The numbers of public transportation users are now increasing, therefore the need for a better transportation system is also crucial, and this condition applicable also to a ferry terminals. Though ferry service is usually among the least chosen way of transportation, but if it is the only way for the commuters to reach their destination, therefore a proper and workable terminals are in need including in Penang. In this research, respondents (commuters) were approached through series of interviews, and questionnaires to evaluate their experience in wayfinding within two ferry terminals of Penang, i.e. the Raja Tun Uda (built in 1960’s), and the newly completed Penang Sentral (November 2018). Respondents approached were the daily commuters, elderly, children, and a first time user. Initial findings show that a proper planning and design of a ferry terminal can help to improve wayfinding experiences within a ferry terminal, hence make the ferry services effective and more efficient.